Ribbon of Peace Banners in Front of Sisk Federal Courthouse - Watkins, Howard::::::::: (1985)
Close up of June Loring with guide dog and Louise Erickson holding up Peace banners with Robin Watkins, Christine Watkins and Adam Watkins viewing them Robin Watkins wearing End [Nuclear] The Race" T-shirt